2021
DOI: 10.1021/acsaem.1c02298
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Construction of the Cobalt Metal Complex Redox Electrolyte and Octahedron Structure of the Cobalt Metal Organic Framework Electrode in the Energy Storage and Energy Conversion System

Abstract: One of the most important tasks in improving supercapacitor (SC) efficiency is the quest for advanced electrode and electrolyte materials. For the first time, we propose using a metal organic framework (MOF) as an electrode and a cobalt redox pair as an electrolyte to increase the cell voltage of a SC. We successfully synthesized the octahedron structure of the cobalt MOF using a simple annealing treatment process, and we prepared a Co-redox couple incorporated along with the KOH electrolyte for the fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Huang et al eventually identified the crystal structure of the nickel−cobalt-mixed MOF through the use of comprehensive Rietveld refinement and ab initio powder XRD techniques. 21 The crystal data published by Huang et al show that the sample's experimental XRD patterns exactly match the modeled ones. Figure 2c shows the crystal structure of the prepared CNN-MOF, CNH-MOF, and CNT-MOF, in which the anchoring organic groups (naphthalene, tricarboxylic, and terephthalate) are directly attached to the sandwich structure between the nickel and cobalt metal layer along the aaxis.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Huang et al eventually identified the crystal structure of the nickel−cobalt-mixed MOF through the use of comprehensive Rietveld refinement and ab initio powder XRD techniques. 21 The crystal data published by Huang et al show that the sample's experimental XRD patterns exactly match the modeled ones. Figure 2c shows the crystal structure of the prepared CNN-MOF, CNH-MOF, and CNT-MOF, in which the anchoring organic groups (naphthalene, tricarboxylic, and terephthalate) are directly attached to the sandwich structure between the nickel and cobalt metal layer along the aaxis.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, Ni/Co-MOF samples in various ratios have the same crystalline structure. Huang et al eventually identified the crystal structure of the nickel–cobalt-mixed MOF through the use of comprehensive Rietveld refinement and ab initio powder XRD techniques . The crystal data published by Huang et al show that the sample’s experimental XRD patterns exactly match the modeled ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy efficiency was computed from charge–discharge curves according to the following equation: Charge and discharge are denoted by E Int / C and E Int / D , respectively.…”
Section: Methodsmentioning
confidence: 99%